2022
DOI: 10.1001/jamadermatol.2021.5866
|View full text |Cite
|
Sign up to set email alerts
|

Association of Spironolactone Use With Risk of Cancer

Abstract: ImportanceWhile originally approved for the management of heart failure, hypertension, and edema, spironolactone is commonly used off label in the management of acne, hidradenitis, androgenetic alopecia, and hirsutism. However, spironolactone carries an official warning from the US Food and Drug Administration regarding potential for tumorigenicity.ObjectiveTo determine the pooled occurrence of cancers, in particular breast and prostate cancers, among those who were ever treated with spironolactone.Data Source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…19 Studies with a score greater than 7 were considered high-quality studies. 20 The risk of bias in RCTs was assessed by using the Cochrane tool for assessing the risk of bias for RCT. 21…”
Section: Methodsmentioning
confidence: 99%
“…19 Studies with a score greater than 7 were considered high-quality studies. 20 The risk of bias in RCTs was assessed by using the Cochrane tool for assessing the risk of bias for RCT. 21…”
Section: Methodsmentioning
confidence: 99%
“…While this study did not assess the effects of spironolactone alone on pCIA, a separate study showed that spironolactone alone was effective in promoting hair growth and inhibiting alopecia progression, at a dose of 200 mg/day [ 89 ]. There had been concerns about spironolactone regarding the hypothetical risk of hormonal stimulation of endocrine receptor-positive tumors [ 93 ]; however, recent studies suggest that spironolactone might actually be linked with reduced cancer incidents [ 94 , 95 , 96 , 97 , 98 , 99 ]. Nonetheless, more extensive research is needed to confirm the effectiveness of spironolactone in treating CIA and assess potential adverse effects.…”
Section: Cia Treatmentmentioning
confidence: 99%
“…This 9-stars scale comprises 3 domains: selection, comparison and exposure/outcome. A score of 7 or higher was considered with high quality(13) (14).…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%